Pelatihan Perakitan Robot Line Following untuk Penguatan Keterampilan Teknik dan Inovasi di SMK 10 Nopember Jakarta - Ariyanti, Silvi; Alfa, Bonitasari Nurul; Lubis, M. Sobron Yamin (CV. IRA PUBLISHING, 2025)
The rapid development of technology and industry requires Vocational High School (SMK) students to possess skills in robot assembly and programming to meet labor market demands. SMK 10 November Jakarta needs to equip its students accordingly, considering that the existing curriculum does not fully cover these practical aspects. Therefore, a community service activity in the form of a Following Robot Assembly training was conducted. The goal was to enhance students' technical competence in robotics and foster innovation. The training involved assembly practicum, programming, and simulation, with the application of sustainability principles. The activity was held at SMK 10 Nopember on May 27, 2025, and was attended by 28 students from grades X and XI. The results demonstrated an improvement in students' Line Following Robot assembly skills, evidenced by a 50% increase in scores between the pre-test and post-test. This improvement reflects the growth in students' technical knowledge and confidence in practical design and problem-solving.